The Financial and Professional Impact of Anterior Cruciate Ligament Injuries in National Football League Athletes - Secrist, Eric S. (Orthop J Sports Med, 2016)
BACKGROUND: Anterior cruciate ligament (ACL) injuries can have negative consequences on the careers of National Football League (NFL) players, however no study has ever analyzed the financial impact of these injuries in this population. PURPOSE: To quantify the impact of ACL injuries on salary and career length in NFL athletes. STUDY DESIGN: Cohort study; Level of evidence, 3. METHODS: Any player in the NFL suffering an ACL injury from 2010 to 2013 was identified using a comprehensive online search. A database of NFL player salaries was used to conduct a matched cohort analysis comparing ACL-injured players with the rest of the NFL. The main outcomes were the percentage of players remaining in the NFL and mean salary at 1, 2, 3, and 4 years after injury. Cohorts were subdivided based on initial salary: group A, <$500,000; group B, ≤$500,000 to $2,000,000; and group C, >$2,000,000. Mean cumulative earnings were calculated by multiplying the percentage of players remaining in the league by their mean salaries and compounding this each season. RESULTS: NFL athletes suffered 219 ACL injuries from 2010 to 2013. The 7504 other player seasons in the NFL during this time were used as controls. Significantly fewer ACL-injured players than controls remained in the NFL at each time point (P < .05). In group A, significantly less ACL-injured players remained in the NFL at 1 to 3 seasons after injury (P < .05), and in group B, significantly less ACL-injured players remained in the NFL at 1 and 2 seasons after injury (P < .05). There was no significant decrease in group C. Players in groups A and B remaining in the NFL also had a lower mean salary than controls (P < .05 in season 1). The mean cumulative earnings over 4 years for ACL-injured players was $2,070,521 less per player than uninjured controls. CONCLUSION: On average, ACL-injured players earned $2,070,521 less than salary-matched controls over the 4 years after injury. Players initially earning less than $2 million per year have lower mean salaries and are less likely to remain in the league than uninjured controls. The careers of players initially earning over $2 million per year, meanwhile, are not negatively affected. This demonstrates the degree of negative impact these injuries have on the careers of NFL players. It also indicates that a player’s standing within the league before injury strongly influences how much an ACL injury will affect his career.